Chief Financial Officers as Inside Directors1. (17th April 2014) - Bedard, Jean C.; Hoitash, Rani; Hoitash, Udi
<x xml:space="preserve">Abstract</x> Considerable prior research investigates whether the extent of insider presence on corporate boards is detrimental. However, the majority of past research treats all inside directors as a homogenous group. This study considers that issue in the context of chief financial officers (CFO) serving on their own company's board. Our research is important because individuals in different executive roles bring different skills and knowledge to board interactions, highlighting the potential for differential contributions. As prior research does not specifically distinguish CFOs from other board insiders, the potential benefits of knowledge sharing due to increased communication with other board members may have been masked. Specifically, the CFO is directly responsible for the quality of the financial reporting process and can therefore be associated with specific outcome measures. Our results show that the percentage of CFOs serving on their own boards is not large, likely due to the perspective (consistent with agency theory and reflected in independence guidelines) that company insiders on boards could promote their own best interest at the expense of shareholders. Contrary to this perception, we find that companies whose CFO has a seat on the board are associated with higher financial reporting quality (i.e., a lower likelihood of reporting a material weaknesses in internal controls or having a financial restatement, and better accruals quality). Yet, we also find potential drawbacks in that CFOs with a board seat tend to have higher excess compensation and lower likelihood of termination following poor performance, signaling greater entrenchment. While our results provide information to companies considering appointing the CFO to the board, both costs and benefits are demonstrated, and thus we conclude that each board should consider this decision based on its own circumstances and composition.